Validity of E-LKPD Based on Liveworksheets to Train Science Process Skills on Plant Cell Structure Material - Wangsa, Indah Kumala Kusuma; Indah, Novita Kartika (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2024)
This research aims to develop e-LKPD on plant cell structure material with the aim of training science process skills that are suitable for use in learning based on validity and practicality,. This research uses a 4-D development model (four-D Models), including defining, designing, developing, and deploying, but the dissemination needs to be carried out in this development research. The research was conducted at the Department of Biology, UNESA, and tested on 33 F1 SMAN 3 Sidoarjo students. The research instruments used were e-LKPD validation sheets, implementation observation sheets, teacher response questionnaires, student response questionnaires, pretest and posttest assessment sheets, and indicator achievement sheets. Data analysis was conducted in a quantitative descriptive manner. The validity result obtained a very valid category with an average of 3.75. The results of the practicality test are very practical in terms of the implementation score of 92.8%, teacher response score of 95.65%, and student response score of 97.73%. Based on these results, the e-LKPD is valid for students at the SMA phase F level.